2020
DOI: 10.1038/s41598-020-60352-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a two-stage limb ischemia model to better simulate human peripheral artery disease

Abstract: peripheral arterial disease (pAD) develops due to the narrowing or blockage of arteries supplying blood to the lower limbs. Surgical and endovascular interventions are the main treatments for advanced pAD but alternative and adjunctive medical therapies are needed. currently the main preclinical experimental model employed in pAD research is based on induction of acute hind limb ischemia (HLI) by a 1-stage procedure. Since there are concerns regarding the ability to translate findings from this animal model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 88 publications
1
41
0
Order By: Relevance
“…We used a model of limb ischemia that was induced by the complete removal of the femoral artery and the closing of its branches. CLIinduced mice were evaluated for functional recovery and ischemia using the Tarlov, ischemia, modified ischemia, function, and the grade of limb necrosis scoring system at days 3, 7, 14, 21, and 28 after cell transplantation [44,45]. The results showed that BM-MSC transplantation improved the treatment efficacy of hindlimb ischemia compared to AT-MSCs and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…We used a model of limb ischemia that was induced by the complete removal of the femoral artery and the closing of its branches. CLIinduced mice were evaluated for functional recovery and ischemia using the Tarlov, ischemia, modified ischemia, function, and the grade of limb necrosis scoring system at days 3, 7, 14, 21, and 28 after cell transplantation [44,45]. The results showed that BM-MSC transplantation improved the treatment efficacy of hindlimb ischemia compared to AT-MSCs and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Third , there are variabilities in the angiogenic processes in different mouse strains ( 78 ). Fourth , we acknowledge that current one stage HLI model ( 81 ) would not allow us to examine the regenerative angiogenesis in details. Thus, anti-inflammatory treatment has been presumed a promising therapy to control the local inflammation and promote desired neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, we show for the first time that improvement in voluntary endurance exercise performance following ET is not associated with enhanced blood flow, oxygenation and/or vascularization in a mouse model of LEAD. During the revision process of our manuscript, Krishna et al 25 reported that 4 weeks of running wheel exercise (30-45 min per day,average distance covered per day: 80-200 m) increased functional capacity (i.e. total distance walked by mice until exhaustion) but not limb perfusion in ApoE −/− mice subjected to a two-stage hindlimb ischemia (i.e.…”
Section: Discussionmentioning
confidence: 92%
“…total distance walked by mice until exhaustion) but not limb perfusion in ApoE −/− mice subjected to a two-stage hindlimb ischemia (i.e. initial gradual femoral artery occlusion by ameroid constrictors for 14 days and subsequent excision of the femoral artery) 25 . These findings are directly in line with our observations.…”
Section: Discussionmentioning
confidence: 96%